Integrative Trends in Future-Ready Education: STEM, ESD, and Artificial Intelligence in Jakarta’s Primary Schools - Bramianto Setiawan; Didit Ardianto; Tustiyana Windiyani (PT. Intelektiva Global Nusantara, 2025)
Amid increasingly complex global dynamics, the integration of STEM (Science, Technology, Engineering, and Mathematics), Education for Sustainable Development (ESD), and Artificial Intelligence (AI) in primary education is crucial. This hybrid research study examines the implementation of these three approaches in Jakarta primary schools through a survey of 50 teachers and in-depth interviews with five school leaders. Findings indicate that while awareness of STEM, ESD, and AI is high, implementation remains uneven, with barriers such as a rigid curriculum, lack of teacher training, and infrastructure gaps—particularly for AI. The study also identifies emerging local innovative practices as examples of success. Implications emphasize the need for systematic policy support, strengthened pedagogy, and multidisciplinary collaboration to achieve sustainable and future-ready education. Limitations of the study include the small sample size, which requires further research for broader generalization